Understand Noise on Universal Quantum Adder Circuit - Methachawalit, Wiphoo; Chongstitvatana, Prabhas (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Quantum Fourier Transform (QFT) is an essential algorithm for quantum computers. There are many uses of QFT in the application of quantum computing. In this work, we proposed a generalized adder circuit that was fundamental for QFT. We designed and ran the experiments with the proposed adder circuit on an IBM quantum computer facility. We observed that the number of qubits was one factor in the error rate. We found that our proposed two-qubits adder circuit running on the IBM quantum computer had an error rate of around 25%. The complexity of the adder circuit includes qubit connectivity, physical devices, and error from noise due to the environment. We demonstrated the constraints of the proposed adder circuit.